Plant defense: ARR11 response regulator as a potential player in Arabidopsis - Falconieri, Gaia Salvatore; Bertini, Laura; Bizzarri, Elisabetta; Proietti, Silvia; Caruso, Carla (Frontiers in Plant Science, 2022)
Plant growth and response to environmental cues are largely driven by hormones. Salicylic acid (SA)- and jasmonic acid (JA)-mediated defenses have been shown to be effective against different types of attackers. SA-mediated defense is mainly effective against biotrophic pathogens and phloem-feeding insects, whereas JA-mediated defense is effective against necrotrophic pathogens and tissue-damaging insects. Cytokinins (CKs) are classic growth hormones that have also emerged as plant immunity modulators. Evidence pointed out that CKs contribute to the defense responses mediated by SA and JA, acting as hormone modulators of the SA/JA signaling backbone. Recently, we identified in Arabidopsis a type-B response regulator 11 (ARR 11) involved in cytokinin-mediated responses as a novel regulator of the SA/JA cross-talk. Here we investigated plant fitness and resistance against the fungal necrotrophic pathogen Botrytis cinerea in Arabidopsis wild-type Col-8 and defective arr11 mutant following SA, JA, CK single or combined treatment. Our results demonstrated that the SA/JA/CK pathway has a positive outcome on plant fitness and resistance against B. cinerea in Arabidopsis Col-8, while the defective arr11 mutant exhibited slightly reduced fitness and increased resistance to B. cinerea infection. This suggests that ARR11 can act as a regulator of the observed traits. The results will provide not only new background knowledge, but also new opportunities for alternative ways of protecting plants from fungal diseases.